10.5k views
2 votes
Can someone do these asap :-)

Can someone do these asap :-)-example-1
User Valentasm
by
5.0k points

1 Answer

3 votes

Answer:

a. m∡ADB = 25°

b. m∡BDC = 35°

c. Used angle addition postulate. It created the equation m∡ADB + m∡BDC = m∡ADC which helped solve for x°

Explanation:

The angle addition postulate states the addition of smaller angles equals the overall angle OR m∡ADB + m∡BDC = m∡ADC

Given:

m∡ADB = x°

m∡BDC = x° + 10

m∡ADC = 60

m∡ADB + m∡BDC = m∡ADC; now substitute

x° + x° + 10 = 60

2x° = 50

x° = 25°; now plug back

m∡ADB = x° = 25°

m∡BDC = x° + 10 = 25° + 10° = 35°

I hope this helps

User Olambert
by
4.5k points